Acute fatal group A Streptococcal primary peritonitis following vaginal delivery. (2020) - Aziz Daghmouri, Mohamed; Affes, Fatma Zahra; Jebri, Alia; Boussassi, Raja; Hamouda, Sonia Ben; Bouguerra, Badreddine; Houissa, Mohamed
Abstract: Acute primary peritonitis due to group A streptococci (GAS) is a rare but life-threatening disease most often seen in case of liver cirrhosis or nephrotic syndrome. The specific mechanism of this infection remains unknown and according to the literature hematogenous, lymphatic, retrograde inoculation from the genitourinary tract and translocation of intestinal tract flora have all been proposed. We report a case of a 37-year-old previously healthy patient who presented to the emergency, four days after vaginal delivery, with abdominal pain and septic shock. Acute peritonitis was diagnosed and peritoneal and blood culture revealed group A streptococci. Unfortunately, the patient died within 12 h despite adequate resuscitation and antimicrobials . The present case report highlights the importance of an early diagnosis with an adequate therapy in case of GAS peritonitis after vaginal delivery.